Social significance of religious camps along Lagos-Ibadan expressway, Nigeria (2021)
Religion has a way of affecting every facet of the life of an individual or group of persons. Human beings are social animals who respond to their natural environments religiously. This response leads to institutionalised religious practises that are observed by adherents. Many religious institutions begin to proliferate and expand their tentacles as they grow. This expansion led to the acquisition of an expanse of land in choice areas among which is the Lagos-Ibadan expressway corridor. Many religious institutions have their campgrounds along the axis, which is over 120 kilometres long. The effects of the activities of these campgrounds have made scholars criticise them and faulted their mode of operations. Hence, the need to consider the social significance of the religious camps along the Lagos-Ibadan expressway, which is what this paper tries to survey. Max Weber’s Social Action theory is adopted in the analysis of the study while employing a simple sampling method of survey. The findings of the survey show that religious camps are socially significant in enhancing social relations and interaction, improving the Standard of living, and improving the availability of social amenities. The paper recommends that religious camps should employ means that will not put worshippers at health risks in their camps.